PARENTING STYLES AND THEIR IMPACTS ON CHILD PROBLEM BEHAVIORS - Sumargi, Agnes Maria; Prasetyo, Eli; Ardelia, Benedicta Winona (Faculty of Psychology, Diponegoro University, 2020)
Managing child problem behaviors as early as possible is crucial. Several studies have shown the impact of parenting on child problem behavior; however, the studies did not investigate the influence of paternal and maternal parenting on child behavior separately. This study aimed to test the effect of mothers’ and fathers’ authoritative and authoritarian parenting on child problem behavior. Furthermore, this study examined the influence of family adjustment on parenting styles. Participants were 105 pairs of parents (fathers and mothers). They completed a set of questionnaires assessing their parenting styles, child problem behavior, and family adjustment. Multiple regression analyses resulted in a significant effect of mothers’ authoritative parenting on child emotional problems, as well as significant effects of fathers’ authoritative and authoritarian parenting on child behavioral problems. Another key finding was that parental teamwork predicted the effectiveness of parenting.